2012
DOI: 10.1002/chem.201200880
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Key Intermediates in Rhodium(I)‐Catalyzed [2+2+2] Cycloadditions of Alkynes by ESI‐MS

Abstract: The mechanism of the Rh-catalysed [2+2+2] cycloaddition reaction of diynes with monoynes has been examined using ESI-MS and ESI-CID-MS analysis. The catalytic system used consisted of the combination of a cationic rhodium(I) complex with bisphosphine ligands, which generates highly active complexes that can be detected by ESI(+) experiments. ESI-MS on-line monitoring has allowed the detection for the first time of all of the intermediates in the catalytic cycle, supporting the mechanistic proposal based mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 73 publications
2
26
0
Order By: Relevance
“…In 2012 an ESI-MS investigation of Rh-catalyzed [2+2+2] cycloaddition reaction was reported [55]. In this DFT-supported study, several key intermediates were observed and characterized by MS/MS tandem spectrometry.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In 2012 an ESI-MS investigation of Rh-catalyzed [2+2+2] cycloaddition reaction was reported [55]. In this DFT-supported study, several key intermediates were observed and characterized by MS/MS tandem spectrometry.…”
Section: Methodsmentioning
confidence: 95%
“…Rhodim-catalyzed [2+2+2] cycloaddition mechanism for of diynes and monoynes based on detected species by ESI-MS and CID characterization[55].…”
mentioning
confidence: 99%
“…The former is a coordinatively saturated intermediate due to the presence of CO. [38] CO-5-Cp is converted by reductive elimination into CO-6-Cp, from which benzene is cleaved by stepwise addition of two acetylene molecules. The conversion of CO-1-Cp into CO-2-Cp is accompanied by the slippage change h 1 !h 3 + h 2 and the release of 65.8 kcal mol À1 .…”
Section: Acetylene [2+2+2] Cyclotrimerization: An Alternative Mechanismmentioning
confidence: 99%
“…For reactive organometallics, this is especially probable since many metals are strongly oxophilic. Such reactions are usually not problematic, as understanding the source of such ions is typically sufficient for correct interpretation, and the promiscuity of ions towards reaction offers an entirely new opportunity to push the instrument beyond a simple means of analysis, and instead using it as a reaction chamber. Details of such reactions are beyond the scope of this perspective (and have been well reviewed elsewhere), but an example from our group is illustrative of the kind of experiment that can be conducted.…”
Section: Gas‐phase Reactionsmentioning
confidence: 99%